2021
DOI: 10.5644/ama2006-124.303
|View full text |Cite
|
Sign up to set email alerts
|

Longterm Antiepileptic Therapy and Bone Health: Implications for Patients with Brain Tumors

Abstract: <p><strong>Objective. </strong>The objective of our study was to investigate the effects of carbamazepine (CBZ) and lamotrigine (LTG) treatment on bone metabolism in epileptic patients.</p><p><strong>Patients and Methods. </strong>A cross-sectional study was performed on normal controls (N=30) and 100 patients with symptomatic epilepsy caused by a primary brain tumor, divided into two groups according to the treatment: LTG monotherapy group (N=50) and CBZ monotherapy g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Offerman et al ( 10 ) first reported the high prevalence of lower VitD status in childhood epilepsy in 1979. Since then, such issues have received widespread attention, and similar findings have been reported ( 55 57 ). Although most studies suggest that ASMs eroded serum VitD levels, it is far from reaching consistent conclusion.…”
Section: Discussionsupporting
confidence: 61%
“…Offerman et al ( 10 ) first reported the high prevalence of lower VitD status in childhood epilepsy in 1979. Since then, such issues have received widespread attention, and similar findings have been reported ( 55 57 ). Although most studies suggest that ASMs eroded serum VitD levels, it is far from reaching consistent conclusion.…”
Section: Discussionsupporting
confidence: 61%